Incidence of hepatocellular carcinoma in chronic hepatitis B virus infection in those not meeting criteria for antiviral therapy - Omar Alshuwaykh; Tami Daugherty; Amanda Cheung; Aparna Goel; Renumathy Dhanasekaran; T. Tara Ghaziani; Aijaz Ahmed; Deepti Dronamraju; Radhika Kumari; Allison Kwong; Mindie Nguyen; W. Ray Kim; et al. (Hepatology Communications, 2022)
Abstract Chronic hepatitis B virus (HBV) infection is the leading risk factor for hepatocellular carcinoma (HCC). The aim of this study was to explore the incidence of HCC in a cohort of subjects with HBV and correlate with HBV treatment current guidance. We identified 2846 subjects with HBV over the study period. HCC was diagnosed in 386 of 2846 (14%) subjects; 209 of 386 (54%) were on nucleos(t)ide analogue (NA) therapy at time of HCC diagnosis, and 177 of 386 (46%) were not on NA therapy. Of the 177 subjects not on NAs who developed HCC during follow‐up, 153 of 177 (86%) had cirrhosis. Within the 177 subjects not on NAs, 158 of 177 (89%) had undetectable HBV DNA, 10 of 177 (6%) had detectable HBV DNA < 2000 IU/L, and 9 of 177 (5%) had HBV DNA > 2000 IU/L. Of those with cirrhosis and undetectable HBV DNA, 115 of 141 had compensated cirrhosis, and 26 of 141 had decompensated cirrhosis. Significant predictors of HCC on time to event analysis included cirrhosis (hazard ratio [HR] 10, 95% confidence interval [CI] 5.8–17.5; p < 0.001), alanine aminotransferase level (HR 1.004, 95% CI 1.002–1.006; p < 0.001), age (HR 1.04, 95% CI 1.03–1.06; p < 0.001), (HR 1.9, 95% CI 1.2–3.1; p 0.007), and nonalcoholic fatty liver disease (HR 1.7, 95% CI 1.1–2.8; p 0.02). Kaplan–Meier analysis demonstrated the cumulative incidence of HCC in subjects with compensated cirrhosis receiving NA therapy was significantly lower compared to subjects with compensated cirrhosis outside current HBV treatment practice guidance (undetectable HBV DNA) (32% vs. 51%; p < 0.001). Conclusion: Those with untreated compensated cirrhosis with undetectable HBV DNA who do not meet current guidance for treatment had higher rates of HCC than those with compensated cirrhosis and suppressed HBV DNA by NA therapy. This study highlights the need for earlier diagnosis and treatment of HBV.